Hypertension and other morbidities with Cushing’s syndrome associated with corticosteroids: a review - Melpomeni Peppa; Maria Krania; Sotirios A Raptis (Dove Medical Press, 2011)
Melpomeni Peppa1, Maria Krania1, Sotirios A Raptis2,31Endocrine Unit, 2Second Department of Internal Medicine-Propaedeutic, Research Institute and Diabetes Center, Athens University Medical School, Attikon University Hospital, Athens, Greece; 3Hellenic National Diabetes Center for the Prevention, Research, Treatment of Diabetes and its Complications (HNDC), Athens, GreeceAbstract: Corticosteroids constitute an ideal treatment for various inflammatory and autoimmune disorders due to their anti-inflammatory and immunomodulatory actions. However, corticosteroids have a considerable number of side effects, including hypertension, diabetes, lipid disorders, sleep apnea, osteoporosis, myopathy, and disorders of coagulation and fibrinolysis, which are components of Cushing’s syndrome (CS). Corticosteroid-induced side effects are dependent on the formulation, route, dose, and time of exposure. However, the underlying pathogenetic mechanisms have not been clearly defined. A large body of evidence supports the role of an imbalance between vasoconstriction and vasodilation with possible links to nitric oxide, prostanoids, angiotensin II, arginine vasopressin, endothelins, catecholamines, neuropeptide Y, and atrial natriuretic peptide. Increased oxidative stress, renin–angiotensin system activation, increased pressor response, metabolic syndrome, and sleep apnea appear to be pathogenetically involved as well. The ideal treatment is the withdrawal of corticosteroids, which is most often impossible due to the exacerbation of the underlying disease. Alternatively, a careful plan, including the proper selection of the formulation, time, and route, should be made, and each side effect should be treated properly. The focus of the research should be to develop synthetic corticosteroids with anti-inflammatory effects but fewer metabolic effects, which so far has been unsuccessful.Keywords: corticosteroids, hypertension, iatrogenic Cushing’s syndrome